2010
DOI: 10.1073/pnas.0913422107
|View full text |Cite
|
Sign up to set email alerts
|

Transience in polarization of cytolytic effectors is required for efficient killing and controlled by Cdc42

Abstract: Cytolytic effectors polarize toward target cells for effective killing and IFN-γ secretion. The spatiotemporal features of this polarization and their importance for cytolysis have not been resolved. In cytotoxic T cells and natural killer (NK) cells, transient polarization was consistently associated with effective killing. Polarization was regulated by Cdc42, a small Rho family GTPase universally critical for cytoskeletal dynamics. Transient accumulation of active Cdc42 at the cytolytic effector/target cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
24
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 35 publications
2
24
0
Order By: Relevance
“…This is in contrast to the early increase in NK cell adhesion, which was evident already after 90 s cell contact. NK cells may therefore be much faster than T cells in establishing cellular adhesion, which is in line with their quick responses during innate immune reactions and that has been suggested to be essential for their effective cytotoxic activity (27). In T cells maximal adhesion forces of ∼14 nN were measured after 30 min contact time (26).…”
Section: Discussionmentioning
confidence: 86%
“…This is in contrast to the early increase in NK cell adhesion, which was evident already after 90 s cell contact. NK cells may therefore be much faster than T cells in establishing cellular adhesion, which is in line with their quick responses during innate immune reactions and that has been suggested to be essential for their effective cytotoxic activity (27). In T cells maximal adhesion forces of ∼14 nN were measured after 30 min contact time (26).…”
Section: Discussionmentioning
confidence: 86%
“…This dynamic remodeling of actin in the center of the IS would depend on Cdc42 in CD4 + T cells thus controlling cytokine release. This could be specific to CD4 + T cells or cytokine release, as Wülfing and colleagues (36) have shown that a dominant negative mutant of Cdc42 does not inhibit granule secretion by CD8 + cytotoxic T cells. What are the downstream regulators of Cdc42-dependent actin remodeling at the IS?…”
Section: Discussionmentioning
confidence: 99%
“…While active Cdc42 is enriched selectively at the center of the CTL/target cell interface, it is spread out over the NK cell/target cell interface. 5 This becomes obvious when the amount of interface accumulation of active Cdc42 is normalized to its area. With such relation to accumulation area, CTLs are much more effective in generating a small area of intense Cdc42 accumulation than NK cells (Fig.…”
mentioning
confidence: 99%
“…Rapid execution of the killing interaction allows a cytolytic effector to kill several target cells sequentially, promoting effective population-wide killing. To maximize cytolytic efficacy, CTLs are fully polarized within seconds of target cell contact with accumulation of signaling intermediates, actin and the MTOC at the CTL/target cell interface, indicative of strong activating signaling 5,14 ( Fig. 1).…”
mentioning
confidence: 99%
See 1 more Smart Citation